Literature Review: The Relationship Between Chronic Energy Deficiency (CED) and The Incidence of Anemia in Pregnant Women - Titi Erina; Atika Zahria Arisanti; Rr. Catur Leny Wulandari1 (LPPM Universitas Harapan Bangsa, 2025)
Chronic Energy Deficiency (CED) is a condition caused by a lack of energy and protein intake over a long period of time. Globally, the prevalence of CED in pregnant women reaches 35-37%. In Indonesia, the prevalence of CED increased to 17.3% in 2018 compared to previous years. Pregnant women with CED are at risk of various complications, such as anemia, bleeding, abnormal weight gain, and susceptibility to infection. The purpose of this literature review is to determine the relationship between CED and the incidence of anemia in pregnant women. The method used was a literature study by reviewing articles from national and international journals. Searches were conducted through Google Scholar, Semantic Scholar, and PubMed using the keywords: